Impact of Self-Regulation Skills on Academic Performance of Young Children in Private Schools of Karachi - Shelina Bhamani; Abeer Kathawala (Journal of Education and Educational Development, 2020)
This research aimed to explore if self-regulation skills had any effecton the academic outcomes of young children in private schools ofKarachi, Pakistan. Quantitative research method was used todetermine the impact of self-regulation upon the academic outcome ofyoung children by utilizing Early School Self-Regulation Scale-Care GiverVersion (Bhamani, 2012).The sample size consisted of randomlychosen 210 children, studying in grades 1 and 2 from seven differentprivate schools in Karachi. The results of the research show that selfregulationskills had a significant impact on the academic outcome ofyoung children in private schools of Karachi, b = -6.3, t (198) = 0.693,p < .01. Self-regulation skills also explained a significant proportion ofvariance in students grades, R2 = .397, F (1, 198) = 130.536, p < .01.
Keywords: academic outcome; children; emotional regulation; private schools; self-regulation